ANALISIS KEPUTUSAN ETIS DI SEKRETARIAT DEWAN PERWAKILAN RAKYAT DAERAH PROVINSI BENGKULU - Yusuarsono - (UNIVED PRESS, Universitas Dehasen Bengkulu, 2015)
This study aimed to determine the Empl oyee Ethical Decision Legislative Council Secretariat Bengkulu province. The research method was qualitative. Informants in this study were all secretariat employees of th e Regional Representatives Council of Bengkulu p rovince. Data was collected by using pur posive sampling technique through interviews. Data analysis was performed through three (3) st ages: reduction, display, and inference and verification. The results showed that ethi cal decision on the Secretariat of Bengkulu Province Council seen from benefits criteria, some decisions are tied to the interest of Council’s member. Seen from rights criteria, the Council membe rs didn’t focus on the rights and interests of all organization or instances and employees. If it’s seen from fairness criteria, the fairness doesn’t applied well for the lazy and diligent employees receive the same honorarium. In addition the appointment of PPTK (Official Technical Users Activity) only employees who are close to the leaders who were appointed. However, because it’s the leader’s decision, all employees must comply. Li kewise with seniority, works often given to senior employees without involving the new on es, so that the new employees are learning slowlyKeywords: Ethical Decision Criteria Benefits, Council, Employee